EVALUASI IMPLEMENTASI KURIKULUM FIK TAHUN2000 MENURUT PERSEPSI DOSEN DAN MAHASISWA - Dimyati Dimyati (LPMPP Universitas Negeri Yogyakarta, 2002)
This article is based on a research conducted to get a description of the implementation of the State University of Yogyakarta' s Faculty ofSports Sciences' curriculum ofthe year of 2000 viewed from the lecturers' and students' perception. The specific aim ofthe research has been to figure out the obstacles found by lecturers and students in implementing the curriculum that year. The research subjects have been the lecturers and students of the course programs known as the PJKR, PKO, and IKORA Course Programs. Quota sampling has been used, obtaining a sample comprising 34 lecturers and 203 students. The sample has also been classified on the basis of representatives for the course subjects and for various fields ofstudy they belong to. Data collection has been done by means of a survey using questionnaires and interviews as well as a curriculum evaluation matrix specifically developed for the re earch. A descriptive data analysis has been conducted on both quantitative and qualitativedata.' From the analysis it is found that the aforesaid curriculum of the year 2000 has been implemented in the three course programs but there have been technical and substantive constraints. (a) The resource books for the lectures have been limited. (b) Many of these books have been in a foreign language. (c) The students' learning process have still been too much dependent on the lecturers. (d) The semester credit points al10cated to some course subjects have not been considered sufficient. (e) There has been a lack of instructional equipment and media. (f) A part of tb.e formulation of tb.e material in tb.e curriculum b.as not been adequately systematic on the basis ofscientific sequencing. The students have not yet been able to ful1y and properly understand the meaning and concept of the curriculum and the teaching-learning process at a university. They have been able to respond only after being stimulated by questions asked in interviews. Nevertheless, the questionnaires and interviews have yielded information concerning their obstacles in implementing the curriculum as fol1ows: (a) many of the resource books have been in a foreign language; (b) there have not been any bound copies of course materials written in Bahasa Indonesia by the lecturers; (c) the lecturers have not explained the syl1abus; (d) learning motivation or interest has been low in relation to certain course subj ects; and (e) it has been difficult to meet the lecturers for final assignment consultation. The limited resource books, many ofthem in a foreign language, and the limited bound copies of course materials in Bahasa Indonesia have caused the students to be unable to learn to an optimum way, particularly in relation with theoretical course subjects whether they belong to the social or exact sciences' group.